PENGARUH CITRA MEREK DAN KUALITAS PRODUK DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL ANTARA TERHADAP LOYALITAS KONSUMEN AIR MINUM MEREK AQUA (Studi Pada Konsumen Aqua yang Berdomisili di Perumahan Puri Anjasmoro) - Lutfiana, Astri Ayu; Saryadi, Saryadi; Wijayanto, Andi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Aqua is a brand of bottled mineral water. The factors predicted affecting consumer loyalty are brand image and product quality. This study aims to examine the influence of brand image, product quality, customer satisfaction, and customer loyalty of Aqua drinking water in the community who are living in Puri Anjasmoro Residential. Type of research is explanatory research. Sampling technique used purposive sampling, which is sampling techniques used based on purpose and specific considerations. The sample size is 97 respondents. Data were analyzed using Validity Test, Reliability Test, Simple Linear Regression, Multiple Linear Regression, Path Analysis. The results of this research prove partially brand image and product quality influence to customer satisfaction. Brand image and product quality simultaneously influence to customer satisfaction. Brand image, product quality, customer satisfaction influence to customer loyalty. Brand image and product quality influence to customer loyalty through customer satisfaction. The conclusion of this study is the influence of brand image on customer loyalty directly by 35,8%. Influence of product quality to customer loyalty directly by 38%. Influence customer satisfaction with customer loyalty directly by 18,1%. Influence of brand image, product quality and customer satisfaction with customer loyalty simultaneously at 66,4%. Influence of other variables outside the model of customer loyalty for 33,6%. The influence of brand image to the satisfaction of 29,3%. Influence the quality of the product to the satisfaction of 44,7%. Influence of brand image and product quality simultaneously to the satisfaction of 47%. Influence of other variables outside the model of customer loyalty for 53%. Research suggest the producer Aqua should maintain and enhance the brand image and product quality to increase customer loyalty.